Evaluating Multidimensional Digital Inclusiveness of Rice Crop Manager Digital Tool: Insights from Indonesia - Singaraju, Niyati; Gakhar, Shalini; Jardinero, Benedict; Pagianti, Tri Selasa; Mendoza, Jared Jorim; Anjana, V (2024)
This study evaluates the multidimensional digital inclusiveness of the Rice Crop Manager (RCM) tool, locally known as Layanan Konsultasi Padi (LKP), in East Java and Yogyakarta, Indonesia. The RCM tool aims to optimize rice farming practices through personalized, data- driven recommendations. Using the MDII framework, the research assesses accessibility, effectiveness, ecosystem support, and impact, based on socio-demographic profiles, digital access, and user perceptions. Findings reveal high land ownership (98%) and smartphone adoption (90%), with significant confidence in the tool’s compatibility and agricultural relevance. However, gaps in digital literacy among older and less-educated farmers, limited mobile internet access (25%), and regional disparities in adoption were identified. Inclusivity concerns persist, with only 68% believing the tool is accessible to marginalized groups. The report highlights the RCM's potential to enhance farming practices but calls for targeted interventions in digital skills, infrastructure, and inclusivity to maximize its impact and adoption